Symmetry and group theory in chemistry - Ameta, R. ([S.l.] : New Age International Pvt. Ltd., 2012)
Symmetry and Group Theory is a powerful theoretical tool to study and predict chemical bonding and spectral properties of molecules. It is only in last three decades that chemists are making use of this tool to understand the fundamental concepts involved in bonding and structure of organic and inorganic compounds.
Keywords: chemistry,symmetry,group theory